2017
DOI: 10.1016/j.jiph.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of digital myiasis

Abstract: Cutaneous myiasis is the infestation of the skin or mucous membranes by larvae of the order Diptera. Wound myiasis affect the skin with a previous lesion, and it may consume both dead and living tissue. Finger infestation is rarely a cause of death, but it may provoke considerable morbidity. Prompt wound exploration and careful total larvae removal is essential to achieve healing. In the reported case, the patient was presented in an advanced stage of the infestation, with a large area of finger necrosis and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Living in rural areas, having a low standard of living, being in close proximity to domestic animals, homelessness, psychiatric illness, diabetes, severe handicap, alcoholism, neurological condition, abuse, and negligence are risk factors for human wound myiasis 2 , 5 , 7 , 10 . In our case, the boy from a low socio-economic background but without any other risk factor, did not inform his parents about the open fracture wound of his great toe because of fear of being scolded.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Living in rural areas, having a low standard of living, being in close proximity to domestic animals, homelessness, psychiatric illness, diabetes, severe handicap, alcoholism, neurological condition, abuse, and negligence are risk factors for human wound myiasis 2 , 5 , 7 , 10 . In our case, the boy from a low socio-economic background but without any other risk factor, did not inform his parents about the open fracture wound of his great toe because of fear of being scolded.…”
Section: Discussionmentioning
confidence: 99%
“…The possible complications of myiasis are local destruction, invasion into deep tissues, and secondary infection, which could result in amputation of the affected area, especially where obligatory parasites are concerned 2 , 5 , 8 . In our case, the wound was extended to the distal phalanx fracture of the right great toe, which might be the complication of myiasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors demonstrate the correlation of the disease with several risk factors. Durão et al (2016) reported digital myiasis in a patient with psychiatric disorder [11]; Giri et al (2015) reported cerebral myiasis in a patient which neglected follow-up consultations [12]; Manjunath and Pinto (2018) reported nasal myiasis in a diabetic patient who presented with recurrent myiasis [13]; Antunes et al (2011) reported a case series of 6 patients that presented psychologic or neurological disorder [14]. At the initial clinical examination, we observed extensive dehiscence in the surgical wound, tissue destruction, necrosis, and a large amount of larvae.…”
Section: Discussionmentioning
confidence: 99%